The role of principal academic supervision in improving the professionalism of teachers of state junior high schools - Joko Winarno; Happy Fitria; Yessi Fitriani (Indonesian Institute for Counseling, Education and Therapy (IICET), 2021)
This study aims to describe the role of the principal in the implementation of academic supervision, the results and obstacles of academic supervision in improving the professionalism of teachers of SMP Negeri in MuaraTelang, Banyuasin District. This research uses qualitative research with a qualitative descriptive approach. The location of this research is SMP Negeri in MuaraTelangBanyuasin District. Data collection was carried out using observation, interviews and documentation. Data analysis using data reduction techniques, data presentation and drawing conclusions. Checking the validity of the findings is done by observing persistence, triangulation and reference adequacy. The results of this study explain the positive and significant role of principal academic supervision in improving the professionalism of teachers of SMP Negeri in MuaraTelang District, Banyuasin. Through discussion of the implementation of academic supervision, the results of academic supervision, and the inhibiting factors for academic supervision of school principals. The results of the supervision carried out by the principal of the State Junior High School in MuaraTelangBanyuasin District were able to improve teacher professionalism in pedagogic competence, personality competence, professional competence and social competence.